Enhancing feedback by health coaching: the effectiveness of mixed methods approach to long-term physical activity changes in nurses. An intervention study - Agnieszka Nerek; Katarzyna Wesołowska-Górniak; Bożena Czarkowska-Pączek (BMC, 2024)
Abstract Background Although knowledge of the barriers and motivators to physical activity participation among nurses is increasing, the factors influencing motivation methods' effectiveness are not completely defined. This study aimed to identify the methods that support increasing the level of daily physical activity and the factors that influence the effectiveness of motivation methods among nurses. Methods This study was based on an intervention study protocol. All registered nurses in clinical settings were invited to participate in the study. The study involved 71 professionally active nurses. A self-reported questionnaire was used to collect sociodemographic and employment data. The level of physical activity was assessed using the International Physical Activity Questionnaire, and the daily number of steps was assessed using a pedometer. Body composition was measured using a bioimpedance method, and the 5-year risk of cardiovascular events was assessed using the Harvard Score. The intervention included self-monitoring daily steps using a pedometer and completing a diary daily for one month. Additionally, a few-minute speech was sent to each participant via email on the intervention's 7th, 14th, and 21st days. Results The analysis revealed a higher value of physical activity recorded in the follow-up compared to the initial and final measurement in the Recreation domain [Met] (p < 0.001) and a higher value of daily steps in the follow-up compared to the final measurement (p = 0.005). Participants with a higher Harvard Score were more likely to increase their daily number of steps (OR = 6.025; 95% CI = 1.70-21.41), and nurses working in hospital wards were less likely to do so (OR = 0.002; 95% CI = 0.00-0.41). Conclusions Recommendations for physical activity in the nursing population should focus on increasing leisure time physical activity and regular risk assessment of cardiovascular events. A mixed methods approach, such as feedback enhanced by health coaching, effectively achieves long-term physical activity changes in nurses.